2017 Japanese guidelines for multiple sclerosis and neuromyelitis optica: Achievements and challenges. Issue 1 (8th February 2018) - Fujihara, Kazuo
Abstract: The 2017 Japanese guidelines for multiple sclerosis and neuromyelitis optica provide comprehensive, updated information and therapeutic evidence for the diseases, and are expected to improve our understanding and management of the diseases. Furthermore, the tasks ahead for the next guidelines are coming into sight. Abstract : 2017 Japanese guidelines for multiple sclerosis and neuromyelitis optica provide comprehensive, updated information and therapeutic evidences of the diseases and are expected to improve our understanding and management of the diseases. Furthermore, the tasks ahead for the next guidelines are coming into sight.